Kondisi Sosial Anak Korban Perceraian Di Kecamatan Sombaopu Kabupaten Gowa - Said, Irwanti; Haruna, Rahmawati (Jurnal Publisitas, 2023)
This research is about the social conditions of children who are victims of divorce in Sombaopu District, Gowa Regency. The results of this research illustrate that divorce has a very negative impact on children's psychological development. Children who grow up in a disharmonious family environment can destroy the child's mentality and morals and the child will experience trauma due to the loss of a figure or figure that they consider to be an example or guide in a household. In these conditions, many of them will experience biological, psychological, and other deviations. The impact of divorce on children's moral development makes them children who are easily influenced by negative environments, such as children who will have a stubborn nature, cannot accept positive input, abuse narcotics and deviate from morals. Moral deviance is an escape for those confused and suffering who don't know what to do. In this case, parents are the first educators for a child so that the child does not experience problems during the child's development and growth process.​